Prarancangan Pabrik Etilbenzena Dari Etilena dan Benzena Dengan Proses UNOCAL/UOP Kapasitas 200.000 Ton/Tahun - Nashruddin, Muhammad, Emi Erawati, S.T., M.Eng, M. Mujiburohman, S.T., M.T., Ph.D (2015)
Ethylbenzene plant design capacity of 200,000 tons per year from ethylene and benzene will use the Unocal/UOP process using Fixed Bed Reactor Multitube with an operating temperature of 180-199.94oC and pressure of 5 atm. The reaction takes place in the phase of preparing ethylbenzene gases, irreversible, and in non-isothermal conditions. The factory is planned to operate for 330 days a limited liability company (PT). Raw material needs for the manufacture of ethylbenzene from ethylene and benzene each as much as 6,696.8853 kg/h and 18,583.0945 kg/hour. Ethylene raw material obtained from PT Chandra Asri Petrochemical Center is capable producing 522,000 tons of ethylene per year, while benzene raw material obtained from Pertamina UP IV Cilacap which has a capacity of 120,000 tons per year and it is possible capacity additions. The resulting ethylbenzene production as much as 25,252.52525 kg / hour. In the process of preparing ethylbenzene as much water as needed 375,027.81 kg/hour to meet the needs of cooling water, 71,091.9896 kg/h for steam, and as much 2399.3050 kg/hr for water sanitation. Ethylbenzene factory will be established in the Cilegon Industrial Estate, Banten, West Java, namely on highway Anyer and will be built on a land area of 28 060 m2, the number of employees as much as 122 people. To establish this ethylbenzene plant needed fixed capital of Rp 713,058,447,472.00 and requires working capital of Rp 368,200,579,411.00 and will make a profit of Rp 203,158,558,665.00 after a tax of 30% of profit before tax amounting to Rp 290,226,512,379.00. Thus obtained precent return on investment (ROI) before tax of 40.70% and after tax amounted at 28.49%. Pay out time (POT) before tax and after tax is for 1.97 years and 2.60 years. Break Even Point (BEP) of 59.30%, shut down point (SDP) of 46.75%, while discounted cash flow (DCF) of 56.12%. Judging from the economic feasibility analysis taking into account the price of ROI, POT, BEP, SDP, for plants with low risk can be concluded that ethylbenzene plant is feasible to set up. Keywords: ethylbenzene, the process of UNOCAL / UOP, Fixed Bed Multitube